A Comparative Study Of Role Of Ritodrine Versus Magnesium Sulphate In Preterm Labour - Jagrati Kiran Naagar; Jyoti Bindal (International Journal of Medical Research and Review, 2015)
Introduction: Preterm delivery which accounts for over 75% of all cases of perinatal mortality and morbidity is the most important obstetric problem of world today.The present study was conducted in the department of obstetrics and gynecology at Kamla Raja Hospital Gwalior. This study is an attempt to study the efficacy of two most commonly used tocolytic agents ritodrine versus magnesium sulphate in controlling preterm labour.Methods: The material for the present study comprised of 100 patients who were in preterm labour out of which 50 were given Ritodrine infusion and 50 were given magnesium sulphate.Both the groups were compared for tocolytic efficacy and effect of preterm labour on neonatal .mortality and morbidity.Result: In the present study >2 days were gained in 28%in Ritodrine group and 26% in magnesium sulphate group.3-6 days gained in 42% cases in Ritodrine group and 46% in magnesium sulphate group.It was observed that maimum time gained in both the groups in majority of cases was up to 6 days.Conclusion: The primary tocolytic agent chosen should be efficient with minimum side effects to mother and fetus. Ritodrine group and magnesium sulphate appears to fulfill these requirements. Magnesium sulphate is found to be comparable to Ritodrine in terms of efficacy and safety. Magnesium sulphate appears cheaper as compare to Ritodrine.